Pit, Spirit, Necromancer or Instrument Used in Necromancy? The Problem of Finding the Correct Meaning of the Hebrew Word אוב (’ôḇ) - Lemański, Janusz (The Biblical Annals, 2024)
Various meanings are attributed to the word אוֹב: pit, spirit, necromancer, instrument for divining the future with the help of the dead. Thus, in some cases, it is difficult to decide on the right word to translate it. This article attempts a diachronic analysis of biblical texts and, based on it, traces the potential semantic development from the original sense of “pit”, “instrument used in necromancy” (1 Sam 28:7–8), through the sense of “spirit of the dead” (Isa 8:19; 19:3; 29:4) to the post-exilic use in the sense of “necromancer/medium” (Lev 19:31; 20:6, 27). Deuteronomistic narratives (2 Kgs 21:6; 23:24) and the later list of forbidden practices in Deut 18:10–11 may indicate the timing of this semantic transformation.